Deciphering Risperidone-Induced Lipogenesis by Network Pharmacology and Molecular Validation - Fu, Yun; Yang, Ke; Huang, Yepei; Zhang, Yuan; Li, Shen; Li, Wei-Dong (Frontiers in Psychiatry, 2022)
Background Risperidone is an atypical antipsychotic that can cause substantial weight gain. The pharmacological targets and molecular mechanisms related to risperidone-induced lipogenesis (RIL) remain to be elucidated. Therefore, network pharmacology and further experimental validation were undertaken to explore the action mechanisms of RIL. Methods RILs were systematically analyzed by integrating multiple databases through integrated network pharmacology, transcriptomics, molecular docking, and molecular experiment analysis. The potential signaling pathways for RIL were identified and experimentally validated using gene ontology (GO) enrichment and Kyoto encyclopedia of genes and genomes (KEGG) analysis. Results Risperidone promotes adipocyte differentiation and lipid accumulation through Oil Red O staining and reverse transcription-polymerase chain reaction (RT-PCR). After network pharmacology and GO analysis, risperidone was found to influence cellular metabolism. In addition, risperidone influences adipocyte metabolism, differentiation, and lipid accumulation-related functions through transcriptome analysis. Intersecting analysis, molecular docking, and pathway validation analysis showed that risperidone influences the adipocytokine signaling pathway by targeting MAPK14 (mitogen-activated protein kinase 14), MAPK8 (mitogen-activated protein kinase 8), and RXRA (retinoic acid receptor RXR-alpha), thereby inhibiting long-chain fatty acid β-oxidation by decreasing STAT3 (signal transducer and activator of transcription 3) expression and phosphorylation. Conclusion Risperidone increases adipocyte lipid accumulation by plausibly inhibiting long-chain fatty acid β-oxidation through targeting MAPK14 and MAPK8.